STUDENTS’ ABILITY IN WRITING A NARRATIVE PARAGRAPH AT THE ENGLISH DEPARTMENT OF BUNG HATTA UNIVERSITY - Lely Refnita; Diniati Jasmin (English Language Education and Current Trends (ELECT), 2022)
This article presents the result of a descriptive research on the students’ ability in writing a narrative paragraph at the English Department of Bung Hatta University. The research sample comprises 37 sophomores and they were selected by using total sampling technique. The data were collected by administering a paragraph writing testand analysed by using a descriptive statistics. The results of data analysis show that most students had very high ability to express the content and to apply mechanics in writing a narrative paragraph, but less than half students had very high ability to use vocabulary and to apply correct grammar. Moreover, the majority of students had moderate ability to organize a narrative paragraph. Based on the accumulative result of data analysis, it can be concluded that the students had a high ability in writing a narrative paragraph, and further research is needed to find out why their ability to organize the paragraph is not high.   REFERENCES Andayani, T &Arono. (2016). Improving Students’ Ability in Writing Narrative Text by Using Picture Series for the Eighth Grade Students of Junior High School. Journal of Applied Linguistics and Literature.2 (2),1-10. Anker, S. 2010. Real Writing with Readings: Paragraphs and Essays for College, Work, and Everyday Life. Boston: Bedford. Aulia, M. D.(2017). Students’ error analysis of cohesive devices in writing narrative paragraph (a case study of the seventh semester students of English Education Department at FKIP UMSU).Jurnal UMSU-Jurnal Online UniversitasMuhammadiyah Sumatera Utara.Retrieved December 6, 2020, from http://repository.umsu.ac.id/handle/123456789/4063 Brown, H. Douglas &Abeywickrama, Priyanvada. (2010). Language Assessment: Pronciples and Classroom Practices (Second Edition). New York: Pearson Education, Inc. Checkett, G. F., &Checkett, L. (2010).The Write Start: Sentences to Paragraphs with Professional and Student Readings. Fourth Edition.Boston: Wadsworth. Evans, V. (2000).Successful Writing Proficiency.Berkshire: Express Publishing. Frestisia, S. (2017).An Analysis of the Second Year Students’ Difficulties in Writing Argumentative Paragraph at English Department of Bung Hatta University.(Unpublished Thesis). Padang: Bung Hatta University. Gay, L.R., Mills, G. E., &Airasian, P. W. (2012).Educational Research: Competencies for Analysis and Applications (10thed.) New Jersey: Parson Education, Inc. Heard, J., Tucker, T. (2016).Advanced Writing: An Accelerated Method for University Students.(E-book Available Online) http://cgpsl.org/wp-content/uploads/2013/11/115.pdf Jayanti, I. D. (2017). An Analysis of the Second Year Students; Ability to Write a Descriptive Paragraph at the English Department of Bung Hatta University.(Unpublished Thesis). Padang: Bung Hatta University. Murthofi?ah, A. (2019). An analysis of grammatical errors in students’ narrative paragraph of the fourth semester students of English Department of IAIN Salatiga in the academic year 2019/2020.Indonesian Journal of Islam and Muslim Societies.Retrieved March 5, 2021, from http://e-repository.perpus.iainsalatiga.ac.id/6369/ Oktawati, H. (2020). Students’ Writing Ability in Narrative Paragraph at Third Semester of English Education Program of STKIP YPM Academic Year 2020/2021.Inovish Journal, 5 (2).Retrieved March, 15, 2021 from http://ejournal.polbeng.ac.id/index.php/IJ/article/view/1708 Pardiyono. (2016). Genre: Mastering English Through Context. Yogyakarta: Andi Offset. Refnaldi., Al-Hafizh, M., &Ardi, H. (2016). Writing: From Paragraphs to Esssays. Padang: UniversitasNegeri Padang. Refnita, L. (2016). Writing: From Sentence to Paragraph. Padang: Bung Hatta University Press. Refnita, L. (2018). Educational Research: A Guide for Beginners. Padang: LPPM Universitas Bung Hatta. Refnita, L. (2020). Writing: From Paragraph to Paragraph. Padang: LPPM Universitas Bung Hatta. Savage, A., &Shafiei, M. (2007).Effective Academic Writing 1: The Paragraph. New York: Oxford University Press. Sonanda, S. N. (2018). Analysis of the Second Year Students’ Problem in Writing a Narrative Paragraph at the English Department of Bung Hatta University.(Unpublished Thesis). Padang: Bung Hatta University. Sunarwan, A. (2016). Increasing Students’ Narrative Paragraph Writing Ability through the Use of Picture Sequence.Pedagogy: Journal of English Language Teaching. 4 (1), 29-39. Yuliani, R. (2018). The First Year Students’ Vocabulary Mastery in Education Topic at English Department of Bung Hatta University.(Unpublished Thesis). Padang: Bung Hatta University.